Miejsce szkoły w pejzażu socjolingwistycznym miasta - Wojtczuk, Krystyna (Acta Universitatis Lodziensis. Folia Linguistica, 1998)
In the article school is treated as an institution which creates its own lexical varieties: pupils’ slang, pedagogic terminology and school common-inflexion vocabulary. Undoubtedly, they influence local language varieties (e.g. in the city) as well as the Polish language itself. Detailed research into this influence should be, according to the author, carried out by Polish sociolinguists in the future.